Building Algerian society between enlightenment and liberation in the thought of the Algerian Muslim Scholars Association - REFICE , Ali (Journal of Social Sciences and Humanities, 2021)
The aim of the research is to highlight the role of the reforming Algerian Muslim Scholars Association in changing the conditions of Algerian society by rebuilding and preserving its identity, as well as its role in resisting the French occupation, and I have used the analytical method, and this is from the point of view of the process of describing the actions and efforts made by scientists The Algerian Muslims, and one of the results of the research is that the reading of the Association of Algerian Muslim Scholars on the reality of Algerian society made it realize that the nation needs to build a person and that the liberation of minds is the basis for the liberation of bodies. The real enemy according to the Association of Scientists is the spiritual spiritual pain Such as in the corners and road deviant and fads and myths, and that if the elimination of colonization, facilitates the elimination of physical colonialism, which is the French occupation, this was a speech Ulama comprehensive as has touched all aspects of the lives of religious and educational, social, economic and political Algerian society.